2021
DOI: 10.1186/s12936-021-03737-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of anti-malarial resistance pfcrt, pfmdr1, and pfk13 polymorphisms in African Plasmodium falciparum imported parasites to Wuhan, China

Abstract: Background Imported malaria parasites with anti-malarial drug resistance (ADR) from Africa is a serious public health challenge in non-malarial regions, including Wuhan, China. It is crucial to assess the ADR status in African Plasmodium falciparum isolates from imported malaria cases, as this will provide valuable information for rational medication and malaria control. Methods During 2017–2019, a cross-sectional study was carried out in Wuhan, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
(64 reference statements)
0
18
2
Order By: Relevance
“…The majority of parasite genotypes were mixed wild-type (i.e., NYT) and variant NFT, which indicates selection by lumefantrine. A newly described mutation was observed at codon 199 ( Table 1 ) ( 33 ), leading to a new haplotype (NYS) that was rare and observed in mixed infections (9.1%). The Pfcrt data indicated that 100% of the parasites were wild type for both single nucleotide polymorphisms (SNPs) genotyped, and mixed infections could not be accurately determined using the capillary sequencing method and thus were not analyzed ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of parasite genotypes were mixed wild-type (i.e., NYT) and variant NFT, which indicates selection by lumefantrine. A newly described mutation was observed at codon 199 ( Table 1 ) ( 33 ), leading to a new haplotype (NYS) that was rare and observed in mixed infections (9.1%). The Pfcrt data indicated that 100% of the parasites were wild type for both single nucleotide polymorphisms (SNPs) genotyped, and mixed infections could not be accurately determined using the capillary sequencing method and thus were not analyzed ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the antimalarial drug resistance of P. falciparum has remained a priority ( 6 , 9 ) and will hamper the global plan for malaria elimination. Therefore, it is necessary to timely monitor the molecular markers involved in drug-resistant Plasmodium and establish an economical, rapid, and accurate detection method.…”
Section: Discussionmentioning
confidence: 99%
“…Detection through nested PCR with sequencing is the most used genotyping technique ( 6 , 8 , 9 ). It is characterized primarily by its high specificity, but the sequencing still requires additional equipment, and the long waiting time is still an open problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations